ISOLASI DAN KARAKTERISASI BAKTERI KITINOLITIK DARI TERASI UDANG - , BRYAN EKA PRAMANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research were to isolate chitinolytic bacteria from shrimp paste and to identify the best isolate in producing chitinase to know its species. Isolation and screening of the bacteria were done by evaluating the chitinolytic index using coloidal chitin agar. The production of crude enzyme was examined by monitoring the absorbance (Î» 280 nm) of the culture which incubated in chitin liquid medium. Optimization of production was determined by observing the growth of isolate and chitinase production of primary metabolites (absorbance 280 nm) at pH 6, 7, 8 and salt concentration 0%